2021
DOI: 10.1186/s13049-021-00844-y
|View full text |Cite
|
Sign up to set email alerts
|

Emergency physician’s dispatch by a paramedic-staffed emergency medical communication centre: sensitivity, specificity and search for a reference standard

Abstract: Background Some emergency medical systems (EMS) use a dispatch centre where nurses or paramedics assess emergency calls and dispatch ambulances. Paramedics may also provide the first tier of care “in the field”, with the second tier being an Emergency Physician (EP). In these systems, the appropriateness of the decision to dispatch an EP to the first line at the same time as the ambulance has not often been measured. The main objective of this study was to compare dispatching an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 28 publications
(14 reference statements)
2
10
0
Order By: Relevance
“…Then, the mean and standard deviation (MSD) is computed across all the R runs. Furthermore, both the receiver operating characteristic (ROC) curve and the area under the curve (AUC; Chappuis et al, 2021 ) indicators are harnessed to provide a graphical plot of measuring our proposed algorithm. ROC and AUC are calculated via the following way: (i) ROC curve is produced by plotting the TP rate against the false-positive rate at various threshold levels.…”
Section: Methodsmentioning
confidence: 99%
“…Then, the mean and standard deviation (MSD) is computed across all the R runs. Furthermore, both the receiver operating characteristic (ROC) curve and the area under the curve (AUC; Chappuis et al, 2021 ) indicators are harnessed to provide a graphical plot of measuring our proposed algorithm. ROC and AUC are calculated via the following way: (i) ROC curve is produced by plotting the TP rate against the false-positive rate at various threshold levels.…”
Section: Methodsmentioning
confidence: 99%
“…It was shown that the advice in providing initial treatment at the scene had a positive effect on both the patient outcome as well as serving to increase the confidence of the EME member. 17,18 However, the benefit of estimating the number of casualties has not been studied in the event of MCIs, which is extremely important in the human resource and medical equipment management areas. Smart glasses can play a crucial role in sustainable development in the medical field in the future.…”
Section: Discussionmentioning
confidence: 99%
“…12 The time from first call to the activation of the PHRM team can vary slightly in SAAS practice. Many cases are immediately activated as per the advanced medical priority dispatch system (AMPDS) 13 protocols. For cases where the clinical need for a PHRM team is not clear, the case will be discussed with a senior medical PHRM specialist working within the ambulance control room environment and exclusively operating in that role (the medical retrieval coordinator).…”
Section: Discussionmentioning
confidence: 99%